Spatial and temporal trends in climatic variables in arid areas of northwest China. (2nd February 2016) - Geng, Qingling; Wu, Pute; Zhao, Xining
ABSTRACT: The trends of major climatic variables at annual and seasonal scales over the past 51 years (1960–2010) in arid areas of northwest (NW) China are investigated using the Mann–Kendall test. From the results it is clear that the majority of the trends (more than 94%) showed significant increasing tendency in three annual temperature indices, including the mean temperature ( T mean ), the mean minimum temperature ( T min ) and mean maximum temperature ( T max ). For T max, however, the significant increase was mainly the result of more significant increases in autumn. The annual and seasonal precipitation ( P ) series showed positive as well as negative trends. Stations with negative trends were mainly located in the Loess plateau for all of the investigated spring, autumn and annual time series. The precipitation trends in the winter exhibited consistently positive values, but most of these trends were not significant. The annual and seasonal wind speed ( U ) decreased significantly at the majority of the stations. More stations showed significant decreasing trends in spring than those in other seasons. The variations in the annual and seasonal relative humidity ( Rh ) series were relatively stable over the region. Most time series showed non‐significant changes, although both positive and negative trends were detected. The results confirmed a particularly strong recent climate change in arid areas of NW China, especially in terms of temperature and wind speed.